Jawabanmu

2014-05-30T19:56:59+07:00
Pembuktian:
cos^4 - sin^4 = (cos^2 - sin^2)(cos^2 + sin^2)
= cos^2 - sin^2
= 1 - sin^2 - sin^2
= 1 - 2 sin^2
terbukti
Jawaban paling cerdas!
2014-05-30T20:02:47+07:00
1. cos^4 A - sin^4 A = (cos^2 A + Sin^2 A)(cos^2 A - Sin^2 A)
diketahui bahwa cos²A+sin²A = 1 maka 1 - sin²A = cos²A
= 1 x (cos²A - Sin²A)= 1 - sin²A - sin²A = 1 -2sin²A

2. cos^4 A + sin^ 4 A= (cos² A + sin² A)² - 2sin² A cos² A
= 1² - 2sin² A cos² A
= 1 - 2sin² A cos² A

3. sin^6 A+ cos^ 6 A = (cos²A + sin² A)^3 -(3sin² A cos^4 A + 3sin^4 A cos²A)
= 1^3 - (3sin²A cos²A (cos² A + sin² A))
= 1 - 3sin²Acos²A
3 4 3